SYSTEMATIC LITERATURE REVIEW (SLR): MENINGKATKAN HASIL BELAJAR SISWA SD MENGGUNAKAN MEDIA LAGU - Astriyani, Gista Ayu; ‘Ulhaq, Jessica Dhiya; Ramandhani, Reskinda; Fakhriyah, Fina; Ismaya, Erik Aditia (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
The main factor in increasing learning activities is the presence of learning that enhances learningactivities, namely the existence of creative and innovative learning in student learning activities. Innovativelearning methods allow students to participate creatively in the learning process so that students do not feelbored and bored when participating in learning activities. An effective and interesting teaching strategy is touse song media in the learning process. This study uses the Systematic Literature Review (SLR) methodwhich aims to identify, observe, and assess research that is relevant to answer questions from researchers.researchers using the Systematic Literature Review (SLR) method have several stages, namely questionsarranged with the topics needed, the process of finding sources used such as sources from Publish or Perishchoosing various sources obtained in accordance with the data used, and examining and selecting the resultsobtained from previous processes such as titles and abstracts are reviewed to determine whether the researchis relevant. Research using tools and materials requires a thorough explanation based on the tools andmaterials used. Singing media is a medium that is good enough to increase students' learning interest inparticipating in learning.